Effectiveness of the Momentum and Impulse Module through Physics Modeling Learning to Improve Scientific Argumentation Skills - Arifuddin, Muhammad; Hany, Ameiy Ray; Mahardika, Andi Ichsan; M, Abdul Salam; Miriam, Sarah; Zainuddin, Zainuddin (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
Students' scientific argumentation ability is important in physics lessons but is still not optimal. Therefore, a teaching module is needed that can help develop this ability. This study aims to produce teaching materials in the form of momentum and impulse modules through effective and feasible physics modeling learning to improve students' scientific argumentation abilities. This study uses the ADDIE development model. The subjects of the research trial were 20 students consisting of 2 classes XI A Boys and XI A Girls of SMA IT Arafah Sampit. The effectiveness of learning reviewed from the student learning outcome test obtained an effective category with an average n-gain score of 0.58 which is categorized as effective in measuring scientific argumentation abilities. Thus, it is found that the use of physics modeling learning through momentum and impulse modules can improve students' abilities in scientific argumentation.